Rural Revitalization and Agricultural Economic Growth in China: Policy Impacts and Structural Transformation - YU, HAI-OU; Manap, Nur Marina Abdul (Research on World Agricultural Economy, 2026)
This study examines the economic effects of China's Rural Revitalization Strategy on agricultural development through an integrated triadic dynamic mechanism framework comprising technological innovation, agricultural industrialization, and industrial structure optimization. Drawing on balanced panel data from 31 provincial-level regions spanning 2013-2022, we employ fixed-effects models, mediation analysis, and dynamic System GMM estimation to systematically identify and quantify transmission pathways and their synergistic interactions. The empirical results demonstrate that rural revitalization policies significantly enhance total agricultural output, with particularly pronounced effects on crop production (coefficient: 1.796), forestry (1.845), livestock (1.093), and fisheries (1.646). Mediation analyses reveal that agricultural industrialization accounts for the largest share of policy impact (62%), followed by technological innovation (46%) and industrial restructuring (17%), confirming their interdependent nature. Regional heterogeneity analysis indicates that eastern provinces exhibit stronger policy responsiveness due to superior fiscal capacity and infrastructure, while central and western regions face resource constraints requiring differentiated policy intensities and longer transformation periods. These findings advance theoretical understanding of rural development mechanisms by demonstrating simultaneous operation of multiple transmission channels rather than isolated pathways. The research provides actionable policy recommendations for enhancing agricultural productivity, promoting sustainable rural transformation, and achieving balanced regional development in China and other developing economies facing similar structural challenges in agricultural modernization. ER